FLYPAPER EFFECT TESTING WITH SEM-PLS MODELS - Armawaddin, Muhamad (Jurnal Ekonomi dan Studi Pembangunan, 2018)
This study aims to test and analyze the phenomenon of flypaper effect of regional expenditure in Southeast Sulawesi province by using SEM_PLS model. Secondary data types use panel data, 17 regencies/municipalities and period 2016-2017. The specific target of this research is to re-test the symptoms of flypaper effect by using SEM-PLS model. The results showed that by using different analysis model, it still found the flypaper effect of regional expenditure shown by the coefficient of influence of transfer fund which is bigger than the coefficient of the influence of Original Income and the influence of indigenous income which is not significant to the expenditure of regencies/municipalities in Southeast Sulawesi. Other Original Regional Original Income is the greatest factor affecting the Local Revenue while the Transfer Fund is a general allocation fund